1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Reduced Microsomal Rat Cytochrome b5

Abstract: The solution structure of the major form of the reduced soluble fragment of rat microsomal cytochrome b, has been solved through 'H-NMR spectroscopy. The protein contains 98 amino acids. Proton assignment was available for residues 1-94, except 90 [Guiles, R. D., Basus, V. J., Kuntz, I. D. & Waskell, L. (1992) Biochemistry 31, 11 365-11 3751 and has been confirmed. From 1722 NOES, of which 1203 were found to be meaningful, a family of 40 energy-minimized structures has been obtained with average backbone rmsd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 57 publications
(46 reference statements)
5
51
0
Order By: Relevance
“…Two propanoate side chains of all tetrapyrrole chromophores in allophycocyanin are accessible from the surface of the protein molecule (51). The two propanoic side chains of the heme in cytochromes (52), myoglobin (53), and hemoglobin (54) also are exposed from the heme pocket, but those of mitochondrial cytochrome c are buried in a crevice (50). In this regard, PhyB appears to resemble the mitochondrial cytochrome c. The phytochrome protein seems therefore to differ from other Table 1).…”
Section: Discussionmentioning
confidence: 86%
“…Two propanoate side chains of all tetrapyrrole chromophores in allophycocyanin are accessible from the surface of the protein molecule (51). The two propanoic side chains of the heme in cytochromes (52), myoglobin (53), and hemoglobin (54) also are exposed from the heme pocket, but those of mitochondrial cytochrome c are buried in a crevice (50). In this regard, PhyB appears to resemble the mitochondrial cytochrome c. The phytochrome protein seems therefore to differ from other Table 1).…”
Section: Discussionmentioning
confidence: 86%
“…Recently, the first structure of CYP17A1 (21) revealed that these arginines form part of a surface-exposed, concave surface on the proximal face of CYP17A1. Conversely, previously determined structures of b 5 show that its heme-binding domain consists of three short helices containing numerous conserved anionic residues framing the partially solvent-exposed heme (22). Mutation of b 5 residues Glu-48 and Glu-49 ablated nearly almost all b 5 effects on in vitro 17,20-lyase activity (23), reaffirming the role of electrostatics.…”
mentioning
confidence: 71%
“…The porphyrin cofactor was included in the structure calculations as previously described. [52,54] The axial and rhombic magnetic susceptibility anisotropies were given as input values and kept constant during the minimization. The 30 conformers with the lowest target function were then used to determine again the anisotropy parameters of the magnetic susceptibility tensors with the program FANTASIA, [49] for the next calculation round.…”
Section: Chembiochem 2002 3 299 ± 310mentioning
confidence: 99%